Isolation of Aspergillus sp. from The Lungs of Sparrows (Passer montanus) - Nugraha, Ronaldi Fajar; Erina, Erina; AK, M. Daud; Jamin, Faisal; Darniati, Darniati (Jurnal Sain Veteriner, 2025)
Aspergillosis is a common respiratory disease in avian species. The infection of Aspergillus sp. is characterized by the presence of yellowish plaques or nodules in the respiratory tract such as the trachea, air sac, and lungs. This study aimed to isolate Aspergillus sp. from the lungs of sparrows. The samples used in this research were the lungs of 35 sparrows taken randomly. Isolation was carried out by Thompson’s method (1969), samples were embedded in Saboraud’s Dextrose Agar (SDA) media and then incubated for 2-7 days. The growth of Aspergillus sp. colonies was observed at 24-hour intervals by looking at the color, shape, edges, and bottom surface of the colonies. Meanwhile, to ensure and confirm the species of Aspergillus sp., the fungus was planted on slide culture media. After that, microscopic observations were conducted by looking at the growth of conidiophores, hyphae, phialids, and fungal conidia. The data obtained were then analyzed descriptively. The result showed that Aspergillus sp. can be isolated from 27 out 35 samples. Based on the result of this study it can be concluded that 77.14% of samples were infected by Aspergillus sp. consisting of Aspergillus niger and Aspergillus flavus.